Caracterización de isoformas del receptor de hormona foliculoestimulante en el ovario bovino - Amherdt, Leandro A. (2021)
The FSH plays an essential role in cattle reproduction. During the estrous cycle of the cattle, said gonadotropin is responsible for the process of ovarian steroidogenesis, growth and follicular maturation. The FSH acts on the ovarian cells through the union to its specific receptor in the plasma membrane of the granulosa cells. In cattle, the concept of an only receptor of FSH (FSHR) is nowadays accepted in order to explain the actions of said hormone on the target cells. However, in those gonads from different species such as ships, rats, mice, cattle and human beings, it has been observed that the ARNm which encodes for the complete receptor (full-length receptor) is co-expressed along with different alternative transcript (isoforms). Therefore, the main objective of this thesis consisted of characterizing the expression patterns of isoforms from FSHR in cattle ovaries for a better understanding about the dynamics of follicular development. Based on the obtained results, it was possible to demonstrate that the exons involved in the creation of variants of FSHR include one or more of the exons 5, 6, 9 and 10. Moreover, it was viable to characterize three variants of the receptor in granulosa cells of cattle antral follicles: FSHR-ISO1 (which lacks exons 5 and 6), FSHR-ISO2 (which lacks exon 9), FSHR-ISO3 (which lacks exons 9 and 10). In addition, the presence of a fourth hypothetical isoform was deduced, FSHR-ISO4 (produced from the simultaneous loss of exons 5, 6 and 9). Regarding the behaviour of said variants, it was possible to establish that while the maturation of antral follicle increases, the primary transcript FSHR wt decreases, as well as the isoforms FSH-ISO1 and FSH-ISO2, and the expression of FSHR-ISO3 is kept invariable. Lastly, we can mention that the isoforms FSHR-ISO1, FSHR-ISO2 and FSHR-ISO4 would present structural modifications at receptor extracellular domain level with possible variations in the affinity towards FSH and the receptor activation. In the case of FSHR-ISO3, the lack of transmembrane domain implies the presence of a soluble receptor. The existence of diverse isoforms of FSH in cattle ovaries could be the result of a regulation mechanism aimed at adjusting the effects of FSH on the different ovarian functions. The results of this thesis provide new knowledge to the understanding of the normal ovarian physiology which, besides, could contribute to the development of new biotechnological tools in order to improve the reproductive efficiency in cattle and livestock production in general.